2012
DOI: 10.1177/1471301211430650
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of an artistic educational program for older people with early dementia: An exploratory qualitative study

Abstract: Objective: To describe a contemporary artistic educational program based on photographic cyanotype techniques and to present the results of the program carried out with older people with early dementia. We determined whether these people could participate in the program, their viewpoint about it, and what this program could contribute to their experience.Method: 21 people diagnosed with mild or moderate dementia participated in a series of artistic education workshops. While conducting the workshops, participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
96
0
25

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(124 citation statements)
references
References 26 publications
3
96
0
25
Order By: Relevance
“…It builds on studies delivered in a gallery setting for people with mild to moderate dementia (e.g. Camic et al, 2014), and people with mild to severe dementia (MacPherson et al, 2009), and in a care-setting for people with mild to moderate dementia (Ullán et al, 2012). However, for the whole sample, scores on the HCS did not change from baseline to time 2, but worsened between baseline and time 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It builds on studies delivered in a gallery setting for people with mild to moderate dementia (e.g. Camic et al, 2014), and people with mild to severe dementia (MacPherson et al, 2009), and in a care-setting for people with mild to moderate dementia (Ullán et al, 2012). However, for the whole sample, scores on the HCS did not change from baseline to time 2, but worsened between baseline and time 3.…”
Section: Discussionmentioning
confidence: 99%
“…Staff reported that some residents, normally withdrawn, were very animated and talkative on the way back from the gallery. Ullán et al (2012) undertook an in-depth qualitative exploration of the process and impact of an artviewing and art-making activity in a day-care setting (n = 21 people with mild to moderate dementia). They found the participants were interested in learning new things, showing improved confidence in their own skills, and capabilities.…”
Section: The Evidence Base For the Arts In Dementia Carementioning
confidence: 99%
“…En los estudios cualitativos se han utilizado para la recogida de datos la observación participante (Ullán et al, 2013); los grupos focales con pacientes, cuidadores y profesionales (MacPherson et al, 2009;A. M. Ullán et al, 2013); y el análisis de contenidos de entrevistas y de grabaciones de audio Camic et al, 2014;Eekelaar et al, 2012;Young et al, 2015).…”
Section: Aspectos Metodológicos De Los Estudiosunclassified
“…Las técnicas utilizadas fueron variadas, tales como el dibujo con pinturas pastel o acuarelas, el modelado con arcilla, el collage (Hattori et al, 2011;Meguro et al, 2009;Rankin et al, 2007;Stallings, 2010;Witkoski & Fagundes Chaves, 2007) o la cianotipia (Ullán et al, 2013). Halpern & O'Connor (2013), para analizar las preferencias estéticas, utilizaron tarjetas con reproducciones de pinturas representativas, casi representativas y abstractas.…”
Section: Aspectos Metodológicos De Los Estudiosunclassified
See 1 more Smart Citation